Regressive Autism Spectrum Disorder: High Levels of Total Secreted Amyloid Precursor Protein and Secreted Amyloid Precursor Protein-α in Plasma - Li, Xiaoli; Zhou, Ping; Li, Qiu; Peng, Bin; Cun, Yupeng; Dai, Ying; Wei, Hua; Liu, Xiao; Yu, Yang; Jiang, Zhiyang; Fan, Qiongli; Zhang, Yuping; et al. (Frontiers in Psychiatry, 2022)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder characterized by social communication difficulties, repetitive behaviors, and parochial interests. Individuals with regressive ASD (RA), a unique subtype, have poor outcomes. Moreover, there are currently no validated blood-based biomarkers for ASD, hindering early diagnosis and treatment. In this study, we first examined plasma levels of total secreted amyloid precursor protein (sAPPtotal), secreted amyloid precursor protein-α (sAPPα), and secreted amyloid precursor protein-β (sAPPβ) in children diagnosed with RA (n=23) and compared them with those in age-matched children with nonregressive ASD (NRA) (n=23) and typically developing (TD) controls (n=23). We found that sAPPtotal and sAPPα levels were significantly higher in children with RA than in children with NRA and TD. In contrast, no difference in sAPPβ level was observed. In conclusion, increased plasma levels of sAPPtotal and sAPPα serve as be early biomarkers of RA. Prospective studies will be conducted using a larger sample to further investigate these differences.